Clinical empathy in GP-training: Experiences and needs among Dutch GP-trainees. "Empathy as an element of personal growth". Issue 12 (December 2021) - Derksen, F.A.W.M.; Olde Hartman, T.C.; Lagro-Janssen, A.L.M.; Kramer, A.W.M.
Highlights: At the start of training emotions rising from empathy complicate medical performance. After a year balance between empathic involvement and carrying out medical tasks. At the end mutual relationship between empathic behavior and personal growth. Explicit attention to the role of GP supervisors and patients in empathy training. Abstract: Objective: Clinical empathy has been described as a key component of effective person-centeredness in patient-physician communication. Yet little is known about general practitioner (GP) trainees' experiences and opinions regarding clinical empathy, empathy-education and the development of empathic skills. This study aimed to explore trainees' experiences with clinical empathy during GP training. Methods: This study used focus group interviews. GP trainees at two Dutch universities were approached by e-mail. Focus groups were conducted between April and November 2018. Six focus groups were conducted: two with starting trainees, two with trainees at the end of their first year and two with trainees at the end of their 3 years' training. Two experienced qualitative researchers analyzed the focus groups. During the thematic analysis the differences and similarities between the various stages of education were taken into account and a framework for the identified themes and subthemes was developed. Results: Thirty-five GP trainees took part. Four main themes could be identified. Starting trainees experienced frictions regarding the influence of personal affective reactions on their medical competencies. Trainees at the end of their first year indicated that they reached a balance between empathic involvement and their responsibility to carry out relevant medical tasks, such as following GP guidelines. Trainees at the end of their three years' training recognized the mutual relationship between the development of the behavioral part of clinical empathy and personal growth. All trainees stated that their needs concerning education changed during their GP training and proposed changes to the curriculum. Conclusions: GP trainees face various obstacles in developing empathic skills and behavior. Particularly they mention handling personal affective reactions. Trainees express a clear wish for clinical empathy, in its theoretical as well as its skill and emotional aspects, to play a central role in the curriculum. Practice implications: More explicit attention to be paid to empathy by embedding theoretical education, explicit attention to skill training and assessment of empathic behavior by patients and supervisors